Continuity Results and Error Bounds on Pseudomonotone Vector Variational Inequalities via Scalarization. (28th January 2016) - Zuo, Xin; Wei, Hong-Zhi; Chen, Chun-Rong
Abstract : Continuity (both lower and upper semicontinuities) results of the Pareto/efficient solution mapping for a parametric vector variational inequality with a polyhedral constraint set are established via scalarization approaches, within the framework of strict pseudomonotonicity assumptions. As a direct application, the continuity of the solution mapping to a parametric weak Minty vector variational inequality is also discussed. Furthermore, error bounds for the weak vector variational inequality in terms of two known regularized gap functions are also obtained, under strong pseudomonotonicity assumptions.